Analisis Kebutuhan Air Daerah Irigasi Malunda Kabupaten Majene - Devy Imanuella Nolan; Herman Welem Tanje; Benyamin Tanan (Paulus Civil Engineering Journal, 2022)
In the Majene Regency of West Sulawesi, the Malunda Irrigation Area is located in the village of Kayuangin covering an area of ​​1122 ha. The need and availability of irrigation water is required because it is an important step in the irrigation system's planning and management. The water balance and the amount of water required are compared in this study to examine the availability of water. The general formula of the Irrigation Planning Standard (KP-03) was used to analyze water demand in this study and water availability using the FJMock method. The need for irrigation water in DI Malunda started in October with a Paddy-Paddy-Parawija cropping pattern. The outcomes of the study of Malunda's water demand obtained a maximum NFR of 0.90 lt/sec/ha and a maximum 80% mainstay discharge of 3.74 lt/sec/ha.